2007
DOI: 10.1007/s00383-007-1891-0
|View full text |Cite
|
Sign up to set email alerts
|

VACTERL anomalies in patients with esophageal atresia: an updated delineation of the spectrum and review of the literature

Abstract: The VACTERL complex refers to anomalies of the bony spinal column (V), atresias in the gastrointestinal tract (A), congenital heart lesions (C), tracheoesophageal defects (TE), renal and distal urinary tract anomalies (R) and limb lesions (L). The incidence of each of these components has not been precisely quantified in the recent literature and the full array of anomalies within each systemic class of the VACTERL complex has not been well described. Therefore, we reviewed our most recent 20-year experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 27 publications
2
45
0
Order By: Relevance
“…For children with EA/TEF, the frequency of associated anomalies identified in the current study was similar to those reported by Quan and Smith in their initial description, by Keckler et al in a review of 112 patients, as well as Brown et al who contacted 579 families of children with EA/TEF from two support groups (Table 6) [2,7,24]. Results are also similar to those reported by Pedersen et al in an analysis of a large European birth defects registry [25].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For children with EA/TEF, the frequency of associated anomalies identified in the current study was similar to those reported by Quan and Smith in their initial description, by Keckler et al in a review of 112 patients, as well as Brown et al who contacted 579 families of children with EA/TEF from two support groups (Table 6) [2,7,24]. Results are also similar to those reported by Pedersen et al in an analysis of a large European birth defects registry [25].…”
Section: Discussionsupporting
confidence: 87%
“…Modern descriptions of the frequency of VACTERL associations in children with EA/TEF and ARM have largely come from single institutional reports with differing criteria, making comparisons difficult [5,7,22,23]. For children with EA/TEF, the frequency of associated anomalies identified in the current study was similar to those reported by Quan and Smith in their initial description, by Keckler et al in a review of 112 patients, as well as Brown et al who contacted 579 families of children with EA/TEF from two support groups (Table 6) [2,7,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may develop respiratory distress due to the following: Diagnosis -A stiff red rubber catheter cannot pass into stomach and it may get arrested at a distance of 8 to 10 cm from the mouth. 7 The diagnosis is confirmed by x-ray studies showing the catheter coiled in the upper oesophageal pouch. 8 It occurs mostly among term and near term babies and is due to delayed clearance of lung fluids.…”
Section: Tracheoesophageal Fistulamentioning
confidence: 62%
“…1 Minimally invasive repair of these fistulas has gained popularity in the past decade as the treatment for cases of EA and TEF. 2 During the repair, the distal TEF is identified and is either ligated with sutures or closed with titanium or polymer locking clips before division.…”
Section: Introductionmentioning
confidence: 99%